Pengaruh Metode Role Playing terhadap Keterampilan Berbicara Siswa Kelas VIII SMP Negeri 1 Kota Bengkulu - Silalahi, Angela Christanti Yoseva; Ariesta, Ria; Yanti, Nafri (UNIB Press, 2025)
This research is motivated by the phenomenon of speaking skills that are considered frightening for the younger generation. The purpose of this study was to determine the effect of the role playing method on the elements of speaking skills in learning observation report texts in class VIII of SMP Negeri 1 Kota Bengkulu. This type of research is a quantitative experimental model research using a quasi-experimental design. The data collected used the values ​​​​on the pretest and posttest by assessing the linguistic and non-linguistic aspects. Data were analyzed using normality tests and homogeneity tests with t-tests or independent sample t-tests. Based on the average pretest in the control class of 57.81 which increased in the posttest value of 66.90. In the experimental class, the average pretest value was 57.69. When given treatment in the form of the role playing method, it increased by 79.11. The test results using IBM SPSS Statistics 25 showed a significance value of 0.000 which was smaller than 0.005. The results showed that the use of role playing in learning on observation report texts had an influence on students' speaking skills in class VIII of SMP Negeri 1 Kota Bengkulu.